1974
DOI: 10.3109/03009737409178402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the Gas Exchange through the Ostium of the Maxillary Sinus

Abstract: Model experiments were performed in order to investigate the gas exchange in the maxillary sinus. The exponent Q2 in the equation illustrating the gas exchange through the maxillary ostium was analysed in relation to the volume of the maxillary sinus, the size of the ostium, the nasal ventilation, the nasal respiratory pressure and the respiratory work. The experiments showed that the gas exchange, expressed as the exponent Q2, is inversely proportional to the size of the maxillary sinus, and principally direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
2
11
0
1
Order By: Relevance
“…This is also supported by the in vivo experiments, where the rapid decline in NO during humming indicated sinus emptying. Previous work has shown that the time needed to exchange all gas in the sinuses varies between y5 min up to 1 h [10,17], with much longer time needed in patients with sinus disorders [10]. The current results indicate that almost the entire sinus volume is exchanged in one single exhalation if the subject is humming.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This is also supported by the in vivo experiments, where the rapid decline in NO during humming indicated sinus emptying. Previous work has shown that the time needed to exchange all gas in the sinuses varies between y5 min up to 1 h [10,17], with much longer time needed in patients with sinus disorders [10]. The current results indicate that almost the entire sinus volume is exchanged in one single exhalation if the subject is humming.…”
Section: Discussionsupporting
confidence: 55%
“…Finally, the respiratory pressure in the paranasal sinuses is similar to that in the nose when the ostia are patent and amounts to y1 cmH 2 O [6]. Earlier studies have shown that ostium size is the most important factor determining sinus ventilation [6,7,10,17], which is also influenced by airflow rate, airway pressure and sinus volume. In the present study all these factors affected the increase in nasal NO during humming and, again, ostium size seemed to be the most important.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The human sinus undergoes a constant pressure-change in routine breathing activities at a frequency of 12–18 times/minute in grown-ups when breathing through the nose, which represents the natural breathing behavior, resulting in a constant pressure change in the maxillary sinus of 5–10 mbar2627 that might add to even significant higher pressure forces at sneezing28.…”
Section: Discussionmentioning
confidence: 99%
“…Также было показано, что только прооперированные околоносовые пазухи с увели-ченными соустьями могут поддерживать концентрацию NO в полости носа за счет возможной в таком случае диф-фузии. Таким образом, предположения R. Aust и B. Drettner [33] о высокой скорости газообмена между полостью носа и околоносовыми пазухами в норме оказались ложными, так как диаметр естественного соустья при отсутствии до-полнительного соустья делает невозможным как меха-низм диффузии, так и активное (при каждом вдохе и вы-дохе) прохождение смеси газов из пазухи в полость носа и обратно. Отсутствие газообмена между полостью носа и околоносовыми пазухами показано в целом ряде исследо-ваний и в настоящее время считается признанным евро-пейским обществом ринологов [11,19].…”
Section: +unclassified